Appropriate treatment for nail breakage following femur intertrochanteric fractures without additional reduction: case series and literature review - Hong Man Cho; Haeryong Heo; Myung Cheol Jung; Woochull Chung; Eunho Choi; Young Lee; Yoon Suh Cho (BMC Musculoskeletal Disorders)
Abstract Background Intramedullary nail breakage is an uncommon complication in patients with femoral intertrochanteric fractures treated with proximal femoral nail antirotation. Salvage surgery for nail breakages associated with delayed union or nonunion is challenging, particularly when breakage occurs within an acceptable reduction range, complicating implant selection. This study evaluated outcomes in patients with proximal femoral nail antirotation breakage, acceptable reduction, and fixation treated with the long proximal femoral nail antirotation change with distal screw dynamization and lateral cortical notching procedure. Methods Eleven patients who underwent the long proximal femoral nail antirotation change with distal screw dynamization and lateral cortical notching procedure between May 2013 and May 2023 with no additional fracture reduction required during salvage surgery and with a helical blade screw resinserted at the same position after removal were observed for > 1 year. Results The average time to full weight-bearing was 8.44 ± 0.82 weeks (mean ± standard deviation) and to return to normal activities was 18.05 ± 0.89 weeks. The Harris Hip Score was 78.64 ± 1.03 at 12 months; all patients resumed independent walking at the final follow-up. The average fracture union time was 21.49 ± 1.75 weeks. In seven cases with a fracture gap at the time of breakage, significant change was observed in the tip-apex distance (P = 0.016) or lateral extension of the proximal femoral nail antirotation blade (P = 0.005) between the immediate post-surgery and final follow-up results, with the gap healing radiographically at 21.50 ± 1.65 weeks. Conclusion Patients with high functional demands, good femoral head bone stock, no acetabular disease, and isolated nail breakage due to nonunion or delayed union in the intertrochanteric area treated with proximal femoral nail antirotation are suitable candidates for osteosynthesis. When reduction is within an acceptable range and the lag screw is centrally placed, long proximal femoral nail antirotation with lateral notching and dynamization offers a minimally invasive approach that reduces soft tissue injury and can yield successful outcomes. Clinical trial number Not applicable.